Determination and Separation of Diarylheptanoids From Alder Growing in Latvia (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The composition of diarylhepatnoids fraction isolated from bark of two alder species (grey alder and black alder) was studied. The efficiency of three extraction methods used for isolation of diarylhepatnoids from alder bark was compared. Two diarylhepatnoids: 1,7-bis-(3,4-dihydroxyphenyl)-heptan- 3-one-5-O-β-D-xylopyronoside (oregonin) and 1,7-bis-(3,4-dihydroxyphenyl)-3-hydroxyheptane-5-O-β-D- xylopyranoside were isolated from the bark of grey alder. The phenolic components of the extracts were analyzed by high-performance liquid chromatography (HPLC). Quantitative determination of oregonin was performed using an internal standard method. The results obtained show that alder barks are rich source of diarylhepatnoids.